Atributinių junginių samprata, aprašymo galimybės ir kai kurie požymiai - Bunevičiūtė, Laima (Kalbotyra, 1998)
Syntax and semantics have become central in linguistics. New trends in grammar have developed new problems in syntax.An attributive words phrase is one of the types of semantic words phrases. Attributive word phrases should be analysed in a new aspect - which begins with meaning and moves to form.The dependent component of attributive phrases denotes a peculiarity, a quality or dependence on a thing expressed by the principal component. The feature of the thing thus indicated is not directly related to the speech act. These phrases are found to have two subgroups 1) qualifying and 2) possessive.The qualifying phrases of the indicated relations denote a thing and its feature, peculiarity or quality, which may be identified directly (e.g., didelis namas, pirmi metai, verkiantis vaikas) or indirectly by a name of another thing (e.g., lauko gėlė, lentyna knygoms, kelias per mišką, etc.).Possessive phrases indicate the belonging of a thing or its other various relations with something (e.g., mano mašina, medžio lapai, tėvo brolis, etc.).No strict line can be drawn between these two subgroups. The transformational method could help to distinguish them.